Formulation of Nutraceutical Products Based on Multigrain and Moringa Leaves (Moringa oleifera L.) as Antistunting Innovations - Rochany Septiyaningsih; Ajeng Puspo Aji; Meyra Alfiah Ananda; Septiana Indratmoko (Postgraduate, University of Mataram, 2026)
Stunting is a nutritional problem that requires innovation in functional food products made from natural ingredients that are nutritious and easy to consume. This study aimed to formulate an anti-stunting nutraceutical product based on multigrain ingredients and moringa leaves (Moringa oleifera L.) in the form of a cereal-like health drink. Product evaluation was conducted through organoleptic testing, pH stability testing, proximate analysis, and hedonic testing. The organoleptic results showed that the three formulations had relatively similar color, taste, aroma, and texture characteristics and remained stable during one month of storage. The pH values were also stable, indicating good chemical stability of the product. Proximate analysis showed that the protein content of 8.14-9.13%, ash content of 1.36-1.74%, and carbohydrate content of 75.15-77.88% met the requirements of SNI 01-4270-1996. However, the moisture content of 7.56-8.01% still exceeded the maximum limit, while the fat content of 4.49-6.19% remained below the standard. The hedonic test results showed that all formulations were accepted and preferred by the panelists, with an average score exceeding 4. Formulation 3 showed superiority in the color parameter, while Formulation 2 was more preferred in terms of taste. Overall, this product has the potential to be developed as an anti-stunting nutraceutical innovation. However, further optimization of the drying process and the composition of fat-source ingredients is still required.